Detection of the Immune Response in Broiler Breeders, and Their progeny to Newcastle Disease Vaccine - Ag’gar, Adil S. (The Iraqi Journal of Veterinary Medicine, 2011)
This trail was suggested to evaluate the amount of inherited haemagglutination inhibition (HI) antibodies for Newcastle Disease (ND) from hens to their own progeny via yolk, blood samples were collected from broiler breeders at 51st week of age aiming the collection their sera, these hens were previously vaccinated with ND-killed vaccine at the age 5 and 120 days respectively via subcutaneous route; and ND-alive vaccine at 1and 18 days then monthly intervals by aerosol, random samples of eggs were collected from panels or hatchery machines either after 24h., to detect amount and location of HI antibodies through them, day old chicks were submitted to the same protocol of blood collection as well as mothers. The results showed that the combination manner of vaccines is an ideal way of HI antibodies peak elevation, these antibodies can pass vertically from dam to progeny through yolk, and the yolk material can be used to detect the HI antibody titer by routine process.